Decoding Earnings Management: The Roles Of Institutional Investors And Tax Planning - Athallah, Muhammad Ariq; Ritonga, Ferdiansyah (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the influence of institutional ownership and tax planning on earnings management in Indonesia’s non-cyclical consumer goods sector from 2019 to 2023. Employing stratified random sampling and multiple linear regression on data from 71 firms, the findings reveal institutional ownership significantly reduces earnings management, while aggressive tax planning increases it. These results highlight the governance role of institutional investors and the risks of tax-driven earnings manipulation. The study offers implications for stakeholders aiming to enhance transparency and oversight in corporate financial practices.